Evolution of Views on the Value of Scientific Knowledge in Western Philosophy - L. A. Pafomova (Дискурс)
Introduction. Evolution of views on the value of scientific knowledge in various directions of Western philosophy, from the ancient period to the 20th century is analyzed in the article. The relevance of the article is due to the fact that the view of scientific knowledge as the value of scientific reality is a fairly new phenomenon.Methodology and sources. The methodological basis of the work is the cultural and philosophical analysis of various points of view in the works of both ancient philosophers, philosophers of the Renaissance and the New times (Plato, Aristotle, Pythagoras, F. Aquinas, Leonard da Vinci, F. Bacon, Locke, Hobbes, Descartes, Spinoza), as well as in the works of O. Comte, Spencer, Mach, Poincare, Pierce, James, Dewey, Jaspers, B. Russell, etc. (i.e. representatives of positivism, existentialism, neo-Thomism).Results and discussion. Today two directions could be distinguished in the relation to science: either its absolutization, that we name scientism, or the cult of an abstract person opposed to science – anthropologism. This is a consequence of the changes in the views on scientific knowledge that have taken place throughout the history of science. Thus, in the ancient period, the value of science was determined, firstly, not in relation to the practical activity of a human being, but only in relation to science to knowledge and cognition, and secondly, as a way of self-development of the individual. In the Middle Ages, science was the “handmaid” of theology. In the Renaissance science faced new challenges: the first was an anti-religious understanding of the essence of a person, the second was the justification of the role of scientific knowledge both for practice and for the worldview as a whole. It was on this understanding of the meaning of scientific knowledge that the concepts of the philosophers of the XVII–XVIII centuries were built, and they dominated until the middle of the XIX century. From this period, a one-sided approach begins to dominate – the ideological role of the value of science was denied and only its pragmatic value is taken. Along with this, there is also a critical attitude towards science, which then develops into anti-scientism. Today, a pessimistic approach (postmodernism, for example) the approach to the consideration of the value of scientific knowledge is characteristic of modern philosophical trends that deny not only the value of scientific knowledge, but also deny knowledge itself.Conclusion. The evaluation of scientific knowledge in Western philosophy has undergone significant changes. If in classical philosophy, with a few exceptions, the recognition of the comprehensive value of science prevailed, i.e. its ideological, humanistic and practical value, then in the future all these three main aspects of the value of scientific knowledge are analyzed. In the extreme forms, this leads to the emergence of antiscientism, for which it is the development of scientific knowledge is perceived as a source of human misery and suffering.